Optimisation Of Apatite Bioceramic Formation From Waste Dental Mould - Osman, Norainin Sofea (Universiti Sains Malaysia, 2018)
According to Advanced Medical And Dental Institute USM (AMDI), the institute disposed 50 kg of dental mould waste per month. Dental mould waste have possibility of calcium source which can form apatite bioceramics materials when react with phosphoric acid. Bioceramics materials synthesis by dental mould waste produced mainly Tricalcium Phosphate (TCP) or Hydroxyapatite (HA) that attracted researcher and scientist attention recently. In this study, it has two projects; synthesis apatite bioceramics from waste dental mould and heat treatment to waste dental mould for reuse it as raw material for making dental mould. For project of synthesis apatite bioceramics material, it used wet chemical precipitation with adopting Chromite Ore Processing Residue (COPR), following by caustic leaching 7M of Sodium Hydroxide (NaOH) solution for single and double time. The result of using 7M NaOH double leaching is able to reduce chromium content from leached residue, which form white color of apatite bioceramic material when react with Phosphoric acid. Main the phase of apatite material will form Tricalcium Phosphate (TCP) after sintered in 1100°C. For 2nd project, dental mould waste undergone heat treatment with 130°C in 2 hour and 160°C in 4 hour times. The waste dental mould can be reuse as POP.